Lithocarpus polystachyus Rehd. ameliorates cerebral ischemia/reperfusion injury through inhibiting PI3K/AKT/NF-κB pathway and regulating NLRP3-mediated pyroptosis - Liu, Daifang; Wu, Wendan; Wang, Tingting; Zhan, Guiyu; Zhang, Yuandong; Gao, Jianmei; Gong, Qihai (Frontiers in Pharmacology, 2024)
Introduction Ischemic stroke (IS) is a serious threat to human life and health, and cerebral ischemia/reperfusion injury (CIRI) exacerbates IS by enhancing neuroinflammation and oxidative stress. Sweet tea (ST) comprises several bioactive components, such as phlorizin, trilobatin, and phloretin, with diverse pharmacological activities. However, it remains uncertain whether ST can confer protection against CIRI. In this study, we aimed to investigate the impact and potential underlying mechanism of ST in the context of CIRI. Methods CIRI model were established in male sprague dawley (SD) rats. The neurobehavioral assessment, the volume of cerebral infarction and the morphology of neurons were measured to complete the preliminary pharmacodynamic study. The therapeutic targets and pathways of ST on IS were obtained by protein-protein interaction, molecular docking and Metascape database. The predicted results were further verified in vivo. Results Our results revealed that ST treatment significantly ameliorated brain damage in rats subjected to CIRI by mitigating mitochondrial oxidative stress and neuroinflammation. Additionally, we identified the PI3K/AKT/NF-κB pathway and the NLRP3-mediated pyroptosis axis as crucial processes, with molecular docking suggested direct interactions between the main compounds of ST and NLRP3. Conclusion ST safeguards against CIRI-induced neuronal loss, neuroinflammation and oxidative stress through the inhibition of the PI3K/AKT/NF-κB pathway and the regulation of NLRP3-mediated pyroptosis.